1995
DOI: 10.1128/aac.39.4.948
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of novel antifolate drug combinations against Plasmodium falciparum and human granulocyte CFUs

Abstract: The potency of antimalarial dihydrofolate reductase inhibitors, alone and in synergistic combination with dihydropteroate synthetase inhibitors, against the Kenyan K39 strain of Plasmodium falciparum (pyrimethamine resistant) and against normal replicating human bone marrow cells in in vitro culture has been studied. Therapeutic indices and rank order of synergistic potency were derived. Trimethoprim, pyrimethamine, and the quinazolines WR159412 and WR158122 had the smallest therapeutic indices (1.39, 4.38, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
4
30
0
Order By: Relevance
“…Clinically, all of these DHFR inhibitors are used in combination with sulfonamides or sulfones. 6,30 A number of studies have shown that resistance of P. falciparum to PSD is correlated with point mutations in both DHFR and dihydropteroate synthase (DHPS). 14-17 Analysis of both genes will likely be required to correlate completely the molecular analysis with the response of parasites to the combination drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, all of these DHFR inhibitors are used in combination with sulfonamides or sulfones. 6,30 A number of studies have shown that resistance of P. falciparum to PSD is correlated with point mutations in both DHFR and dihydropteroate synthase (DHPS). 14-17 Analysis of both genes will likely be required to correlate completely the molecular analysis with the response of parasites to the combination drug.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] The DHFR inhibitors are always used clinically in combination with sulfonamides or sulfones. 2,6,30 Currently, pyrimethamine plus sulfadoxine (PSD) is replacing chloroquine as the first-line antimalaria drug in many countries in Africa. 30 Unfortunately, alleles with mutations at S108N, N51I, and C59R have already been observed in this region; this combination is strongly correlated with decreased susceptiblity to PSD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also active against P. vivax sistance to the triazines has been demonstrated for plasmodia. In addition to the potency of triazines, the very high avidity of this compound for the P. falciparum DHFR differs from its avidity to mammalian DHFR (13)(14)(15), increasing the therapeutic/toxic ratio.…”
mentioning
confidence: 99%
“…In the early 1980s, WR99210 was shown to selectively inhibit parasite growth in vitro, with a 50% inhibitory concentration (IC 50 ) in the nanomolar range (24). Despite better selectivity for the malaria parasite enzyme than for the enzyme in human cells in culture (42), trials of WR99210 with humans showed serious problems of bioavailability, and further development was abandoned. However, Canfield and colleagues (4) demonstrated that in vivo, the biguanide precursor of WR99210, PS-15, is converted to the active triazine form and that this formulation improved the bioavailability substantially.…”
mentioning
confidence: 99%